Breast cancer in the elderly, in men and during pregnancy. Issue 2 (February 2022) - Garreffa, Emanuele; Arora, Deeksha
Abstract: Female breast cancer is the most common tumour diagnosed worldwide and is one of the leading causes of cancer-related death. The management of elderly, male and pregnant patients with breast cancer requires some additional considerations which are reviewed in this chapter. Breast screening is routinely offered to women aged between 50 and 70 years in England. There are substantial regional variations among UK hospitals in the clinical management of elderly breast cancer patients. Primary endocrine therapy is used in the treatment of ER-positive elderly breast cancer patients not fit for surgical intervention. Male breast cancer is rare, accounting for less than 1% of all breast cancers. It is more common in elderly men and tends to behave like post-menopausal breast cancer. Although breast cancer is one of the most frequently diagnosed malignancies among pregnant women, breast cancer during pregnancy is a rare condition and has been associated with more aggressive, high-grade, poorly differentiated tumours and with a predominance of more aggressive molecular subtypes such as triple negative, HER-2-positive and lower rates of ER and PR expression.